Streptococcus pyogenes emm Type 3.93 Emergence, the Netherlands and England - Matthew A. Davies; Brechje de Gier; Rebecca L. Guy; Juliana Coelho; Alje P. van Dam; Robin van Houdt; Sébastien Matamoros; Marit van den Berg; Patrick E. Habermehl; Kartyk Moganeradj; Yan Ryan; Steve Platt; et al. (Emerging Infectious Diseases)
A global increase in the incidence of invasive group A Streptococcus (iGAS) infections was observed after lifting of COVID-19 related restrictions in 2022, and type M1UK dominated in many countries. After seasonal declines in iGAS incidence during the summer of 2023, simultaneous, rapid expansion of a previously rare emm type 3.93 was seen beginning in November, increasing to 20% of all cases in England and 60% of all cases in the Netherlands within 4 months. emm3.93 was associated with iGAS in children 6–17 years of age and with increased risk for pneumonia or pleural empyema and meningitis in both countries. No excess risk of death was identified for emm3.93 compared with other types. Genomic analysis of historic and contemporary emm3.93 isolates revealed the emergence of 3 new clades with a potentially advantageous genomic configuration. Our findings demonstrate the value of molecular surveillance, including long-read sequencing, in identifying clinical and public health threats.